Genome-wide bioinformatics analysis of the MATE gene family for abiotic stress tolerance in sunflower (Helianthus annuus L.) - Mohammad Nazmol Hasan; Md. Robin Islam; Rafee Shahrier; Md. Bayazid Hossen (PLoS ONE, 2026)
Abiotic stressors, such as drought, salinity, and heavy metals, induce physiological changes, nutritional imbalances, molecular alterations, and oxidative stress in plants, which significantly reduce productivity. However, the secondary transporters, multidrug and toxic compound extrusion ( MATE ) proteins, transport substrates and metabolites. Accordingly, in response to abiotic stressors, these proteins strengthen plants’ immune systems, detoxify toxins, and enhance growth and development. Although the roles of MATE proteins responding to abiotic stresses have been investigated in several plants, their functions in sunflower have not yet been discovered. Therefore, this study identified 74 MATE proteins in sunflower ( HanMATE ) based on phylogenetic analysis, which were distributed into four subgroups. Their MATE -like properties were then validated using the domain, motif, gene structure, gene duplication, and physicochemical analysis. The HanMATE proteins in various cell organelles play a crucial role in abiotic stress tolerance, scavenging reactive oxygen species (ROS), and regulating transcription. Subsequently, Most HanMATE genes are enriched with biological processes and molecular functions that transport micro- and macro-molecules, drugs, negatively charged ions, organic anions, and citrate. The important Cis -regulatory elements (CREs), abscisic acid-, light-, and MeJA-responsive elements in HanMATE genes regulate plants’ growth and development in stress conditions. The synteny analysis indicated that 41 HanMATE proteins exhibit over 75% sequence similarity with 40 established stress-responsive (SR) MATE proteins from various plant species, suggesting their potential SR characteristics. Furthermore, this study identified 136 microRNAs linked to 58 HanMATE proteins, including 19 major hub microRNAs and 31 hub HanMATE proteins, which may enhance sunflower agronomic traits and abiotic stress resistance. The HanMATE proteins are conserved in other species that contribute to detoxification and have stable binding affinity with flavonoids and citric acid, validated from 3D structural modeling, molecular docking (MD), dynamic simulation, and functional prediction. These findings demonstrate that HanMATE genes are essential for sunflower abiotic stress tolerance (AST), and genetic engineering can be applied to develop more robust sunflower.